Satisfacción al usuario en la Cooperativa de Transporte “Cia Isla de Bejucal” del Cantón Baba, en el periodo 2023. - Arriciaga Botto, Esteban Adonis (2024)
In the case study on the transport cooperative "Cía. Isla De Bejucal" in Cantón Baba, the focus has been on developing strategies to improve customer satisfaction and thus increase sales. The analysis seeks to keep current customers satisfied and loyal, reducing the need for investment in attracting new customers, resulting in greater long-term profitability. The goal is to motivate the owner to implement tactics that ensure high user satisfaction by solving the problems identified in the study. The survey of regular customers provided suggestions for improving satisfaction. It was concluded that by prioritizing user satisfaction, the cooperative will be able to improve its reputation, establish personalized and constant communication with clients, generate recommendations and referrals, optimize financial resources, and reduce expenses in advertising campaigns. It is expected that these strategies will contribute to an increase in profits by having a satisfied and committed customer base.